A SCIENTOMETRIC ANALYSIS OF PUBLICATIONS ON ACCELERATOR-BASED RESEARCH FROM NUCLEAR SCIENCE CENTRE AND TATA INSTITUTE OF FUNDAMENTAL RESEARCH, INDIA - V. K.J, Jeevan; B.K., Sen (Malaysian Journal of Library and Information Science, 2017)
The study is based on the journal publications generated by the Nuclear Science Centre (NSC) [now known as Inter University Accelerator Centre] and the Accelerator Group at the Tata Institute of Fundamental Research (TIFR) during 1997-1999. The data was collected from the annual reports of the two institutions and analyzed using scientometric tools and techniques. The impact was examined with the help of Science Citation Index (SCI). The analysis highlights yearly output, publication in national or international journals, number of papers in SCI-journals and non-SCI journals, normalized impact factor (NIF) per paper, category-wise distribution of papers in different NIF ranges, the proportion of high NIF papers, papers above the average NIF. NSC is a facility exclusive for accelerator research and its Annual Report gives clear indication of the different specializations, hence the data for NSC is further analyzed in three subdivisions of nuclear physics, materials science, and radiation biology and others. However, such an analysis for TIFR was not attempted due to the lack of such information in its Annual Report. From the study one can have an idea about the performance and impact of the research conducted in the two institutions.